Hubungan antara Kepatuhan Konsumsi Tablet Tambah Darah dan Ukuran Lingkar Lengan Atas Ibu Hamil dengan Kejadian Stunting di Provinsi Nusa Tenggara Timur - Lulu'an Munirah; Sri Sumarmi; Emyr Reisha Isaura (Universitas Airlangga, 2023)
Background: Stunting is the highest health problem in East Nusa Tenggara Province for the past decade. Several factors cause stunting are lack of energy and adherence to consume of iron supplement tablets in pregnant women. Objectives: To analyze the relationship between compliance of taking supplementary blood tablets and the size of the upper arm circumference of pregnant women and stunting incidence in East Nusa Tenggara Province. Methods: This study used secondary data from basic health research (RISKESDAS) in 2018. The sample for this study used children aged 3-5 years and the biological mother as many as 1755 respondents. The test of the relationship using the Pearson Correlation test and the strength test of the relationship using the logistic regression test. Results: The results of this study showed that 72.3% of pregnant women were not compliant to take iron tablets and 23.1% of pregnant women experienced chronic energy deficiency or an upper arm circumference of less than 23 cm. The results of the data analysis showed that there was no relationship between adherence to blood supplement consumption of pregnant women and the incidence of stunting (p=0.910) and there was a relationship between the size of the upper arm circumference of pregnant women and the incidence of stunting (p<0.001). Conclusions: The conclusion of this study is that there is a relationship between the size of the upper arm circumference of pregnant women and the incidence of stunting in East Nusa Tenggara Province.